Climate and the Destination Choice of German Tourists - Jacqueline M. Hamilton (Fondazione Eni Enrico Mattei (FEEM), 2004)
The attractiveness of a tourist destination is partly dependent on its environmental and climatic resource base. Climate change can be expected to have an effect on this attractiveness and will subsequently alter patterns of demand. An application of the pooled travel cost model using survey data on the destination choices of German tourists is presented in this study. Data on the climate, beach length and indicators of cultural, natural resource and economic attractiveness of the destination countries are used in the regression analysis. Optimal climate values were calculated and a climate index was used to examine the change in climatic attractiveness under an arbitrary scenario of climate change. It was found that, for European countries during the summer months, there would be an increase in attractiveness. However, the northern European countries become relatively more attractive closing the gap on the currently popular southern European countries.
Keywords: L83; Q26; Q54; 330; Tourism demand; Climate change; Travel cost model; Internationaler Tourismus; Deutsche; Umweltbewertung; Klima; Welt